1999
DOI: 10.1098/rspa.1999.0386
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of isotropic fibre suspensions

Abstract: The electrical conductivity of a quiescent isotropic fibre suspension is measured for a concentration range nL 3 = 0.1-4, where n is the number density of fibres and L is the fibre length. In the dilute concentration regime, for which nL 3 1, our experiments agree with available theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Nsom (1994) presented the results of a theoretical study of dilute and semi-concentrated suspensions of sti ÿbers, in which the drag reduction is directly computed with respect to the cylinder radii ratio, the ÿber concentration and density. In addition, it is reported that a minimum of highly conducting ÿbers enhances the thermal and electrical conductivity of composites (Mackaplow et al, 1994;Sundararajakumar and Koch, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Nsom (1994) presented the results of a theoretical study of dilute and semi-concentrated suspensions of sti ÿbers, in which the drag reduction is directly computed with respect to the cylinder radii ratio, the ÿber concentration and density. In addition, it is reported that a minimum of highly conducting ÿbers enhances the thermal and electrical conductivity of composites (Mackaplow et al, 1994;Sundararajakumar and Koch, 1999).…”
Section: Introductionmentioning
confidence: 99%